Triumph forsaken : the Vietnam war, 1954-1965 - Moyar, Mark, 1971- (Cambridge University Press, 2006)
"Drawing on a wealth of new evidence from all sides, Triumph Forsaken overturns most of the historical orthodoxy on the Vietnam War. Through the analysis of international perceptions and power, it shows that South Vietnam was a vital interest of the United States. The book provides many new insights into the overthrow of Ngo Dinh Diem in 1963 and demonstrates that the coup negated the South Vietnamese government's tremendous, and hitherto unappreciated, military and political gains between 1954 and 1963. After Diem's assassination, President Lyndon Johnson had at his disposal several aggressive policy options that could have enabled South Vietnam to continue the war without a massive US troop infusion, but he ruled out these options because of faulty assumptions and inadequate intelligence, making such an infusion the only means of saving the country." http://www.loc.gov/catdir/enhancements/fy0642/2006008555-d.html.